Investigation of Participation in Physical Therapy and Rehabilitation Program After Traffic Accidents With Injuries: Traffic Accidents With Injuries And Physical Therapy - Özberk, Sema; Can, Gerçek (The Bulletin of Legal Medicine, 2021)
Objective: Physical limitations in traffic accidents with injuries reduce the functional level and reduce the quality of life. In our study, we aimed to examine the participation of patients who applied to Department of Forensic Medicine for the determination of the rate of disability due to injuries caused by an accident, to physical therapy and rehabilitation programs for sequelae and treatment.Methods: The data of 114 cases were examined in a prospective, descriptive study. The average age of the subjects participating in the study was 36.25 ± 13.38 and their gender distribution was 43 (37.7%) female and 71 (62.3%) male.Results: While 42 (36.8%) of the cases participated in the physical therapy and rehabilitation program at least once due to traffic accident injury, 72 (63.2%) did not. As a result of the statistical analysis, it was found that there was no significant difference in participation in the physical therapy and rehabilitation program according to age, gender, education level and injury site.Conclusion: We think that participation in the physical therapy and rehabilitation program will increase the quality of life with the contribution it will provide at a functional level.
Keywords: ‘Traffic accident’, ‘Sequela’, ‘Physical therapy rehabilitation’